Evaluation of the Stunting Reduction Program: The Role of the Family Assistance Team in Sigi Regency - Nurfatimah, Nurfatimah; Usman, Hastuti; Ramadhan, Kadar (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Stunting is a serious health problem in Indonesia, which can affect the growth and development of children. The Family Assistance Team (FATS) has an important role in stunting prevention through education and nutrition monitoring. This study aims to assess the knowledge, attitudes, and practices of FATS in preventing stunting, as well as identify the challenges faced in the implementation of their duties. The research method used is a descriptive design with a quantitative approach, involving 35 FATSs working in 13 stunting locus villages in Sigi Regency. Data collection was carried out through a questionnaire that measured the knowledge, attitudes, and practices of the FATS, and the data was statistically analyzed to get an overview of the characteristics of the respondents and the effectiveness of the FATS. The results show that FATS has a good understanding of stunting, but there is a need for improvement in terms of resource availability and training frequency. Most FATSs feel effective in their roles and are satisfied with the support provided by their respective organizations. Recommendations for continuous training and adequate logistical support were identified as key to improving the effectiveness of FATS in stunting prevention, providing important insights for the development of more effective stunting prevention programs at the village level.